Critical discourses in the culture-public relations relationship - Daymon, Christine; Surma, A. (BledCom, 2009)
In this essay, we problematise some of the foundations of the culture-public relations relationship and then consider what insights and challenges may be gleaned for the discipline, research, and education. We employ the concept of discourse as a heuristic to aid insight into how culture and public relations intertwine in a dynamic, socially constructed process of meaning making. In identifying two prevalent discourses which inform thinking and writing about culture, we note how these highlight the complexity of the public relations-culture interaction, an aspect often under-estimated in research. We offer some final, tentative ideas concerning both the teaching of public relations and the doing of public relations research.